Added sugar intake and its associations with incidence of seven different cardiovascular diseases in 69,705 Swedish men and women - Janzi, Suzanne; González-Padilla, Esther; Ramne, Stina; Bergwall, Sara; Borné, Yan; Sonestedt, Emily (Frontiers in Public Health, 2024)
The adverse health effects of sugar-sweetened beverage intake are well-established, but the implications of overall added sugar intake remain unclear. We investigated the associations between intake of added sugar and various sugar-sweetened foods and beverages and risk of 7 cardiovascular diseases in 69,705 participants aged 45-83 years (47.2% female) from the Swedish Mammography cohort and Cohort of Swedish men. Questionnaire-based diet and lifestyle assessments were administered in 1997 and 2009. National registers were used for ascertainment of ischemic stroke (n=6,912), hemorrhagic stroke (n=1,664), myocardial infarction (n=6,635), heart failure (n=10,090), aortic stenosis (n=1,872), atrial fibrillation (n=13,167), and abdominal aortic aneurysm (n=1,575) until December 31st, 2019. The associations were studied using cox regression with time-updated exposure and covariate data. Added sugar intake was positively associated with ischemic stroke and abdominal aortic aneurysm, although the highest risks of most outcomes were found in the lowest intake category. Positive linear associations were found between toppings intake and abdominal aortic aneurysm, and between sweetened beverage intake and ischemic stroke, heart failure, atrial fibrillation, and abdominal aortic aneurysm. Negative linear associations were found between treats intake (pastries, ice cream, chocolate, and sweets) and all outcomes, and between toppings intake (table sugar, honey, jams, and marmalades) and heart failure and aortic stenosis. The findings suggest that the associations between added sugar intake and cardiovascular diseases vary by disease and source of added sugar. The findings emphasize the adverse health effects of sweetened beverage consumption and indicate higher cardiovascular diseases risks with lower treats intake, which warrants further investigation.